Exceptions as Rules of the Game for Young Adults: A Close Reading of Sonya Sones’ What My Mother Doesn’t Know - Adhikari, Hari (Literary Studies, 2016)
Adolescents often surprise adults with their exceptional behaviors. Overwhelmed by their struggles for separating from parents, understanding the changes in the body, facing peer pressures, learning to socialize, finding a partner, and discovering one’s position in the society, young adults act in “abnormal” ways. At times they even appear as if they have mad-like obsessions for exceptions. This paper digs out the major concerns of young adults and the strategies to deal with this demography implicitly proposed in Sonya Sones’ novel What My Mother Doesn’t Know. By using Julia Kristeva’s formulations of the notions of “adolescence” and “abjection,” the paper argues that the primary cause of conflicts between adults and young adults is the latter’s “syndrome of ideality” and the adults’ failure to understand them. Empathy from both sides is the key to mutual understanding during their struggles for self-discovery.